Control and management of congenital Chagas disease in Europe and other non‐endemic countries: current policies and practices. Issue 5 (17th March 2016) - Soriano‐Arandes, Antoni; Angheben, Andrea; Serre‐Delcor, Nuria; Treviño‐Maruri, Begoña; Gómez i Prat, Jordi; Jackson, Yves
Abstract: Objectives: Identifying pregnant women infected with Trypanosoma cruzi is one of the major challenges for preventing and controlling Chagas disease (CD) in non‐endemic countries. The aim of this paper was to perform a policy evaluation of the current practices of congenital Chagas disease (CCD) control in non‐endemic countries and to propose specific targets for enhanced interventions to tackle this emerging health problem outside the endemic areas of Latin America. Methods: We conducted a mixed method review of CCD policy strategies by searching the literature in the PubMed, Google Scholar and the World Health Organization (WHO) databases using the key terms 'CCD', 'paediatric Chagas disease' and 'non‐endemic countries'; as free text and combined as one phrase to increase the search sensitivity. Reviews, recommendations, guidelines and control/surveillance programme reports were included. Results: Of 427 CCD papers identified in non‐endemic countries, 44 matched the inclusion. Although local programmes were launched in different countries with large numbers of Latin American immigrants, there were considerable disparities in terms of the programmes' distribution, delivery, integration and appropriated CCD control strategies. Moreover, Catalonia, Spain is the only region/country with an established systematic monitoring of CCD in pregnant women from Latin American countries. Conclusions: Given the worldwide dissemination of CD, the nature of its vertical transmission, and the gaps of the current strategies in non‐endemic countries, there is an urgent need to standardise, expand and reinforce the control measures against CCD transmission.